2017
DOI: 10.1186/s12894-017-0219-1
|View full text |Cite
|
Sign up to set email alerts
|

Transperineal template-guided saturation biopsy aimed at sampling one core for each milliliter of prostate volume: 103 cases requiring repeat prostate biopsy

Abstract: BackgroundWe evaluated the cancer detection rate of prostate cancer using transperineal template-guided saturation biopsy aimed at sampling one core for each milliliter of prostate volume for patients requiring repeated prostate biopsies.MethodsIn total, 103 consecutive patients with repeated prostate biopsies were enrolled in this retrospective study. The number of biopsy cores was defined by prostate volume. In principle, one biopsy core covered 1 mL of prostate volume. We used a prostate brachytherapy templ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…This number is the highest among all reports about TTSB. 18 Lee et al 20 reported that a high number of cores predicts PCa in patients who were diagnosed with HGPIN at a previous biopsy. These facts may contribute to the high detection rate of PCa in patients who had two or more cores of HGPIN at a previous TRUS-guided biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This number is the highest among all reports about TTSB. 18 Lee et al 20 reported that a high number of cores predicts PCa in patients who were diagnosed with HGPIN at a previous biopsy. These facts may contribute to the high detection rate of PCa in patients who had two or more cores of HGPIN at a previous TRUS-guided biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported on the TTSB method that we used in this study. 18 A transrectal probe (Toshiba Medical, Tochigi, Japan) that was attached to a brachytherapy stepping unit (AccuSeed, Bedfordshire, UK) was inserted into the rectum. The low-echoic area was estimated, and the prostate volume was calculated by using the following formula: length × width × height × 0.5236.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…257 The extensive histologic heterogeneity as measured by Gleason score differences within an individual cancer mandates multiple sampling of tumor at the same procedure, 258 at times using a saturation technique, extending to 12 or more needle biopsies. 258,259 To enhance adequacy, much effort has been made to improve the approach route for needle biopsy 260,261 and, in needle design, to increase core length. 255 Accuracy of needle targeting is affected by mode of imaging guidance 262 and by tip deflection, which in turn is affected by prostate size and tissue texture.…”
Section: Prostatementioning
confidence: 99%
“…A special template with holes is placed on the perineum, then needles go through it into the prostate gland [32,35]. In this method, number of cores depends on the gland volume [36]. Whereas during targeted biopsy the MRI scan is used and, as a result, fewer samples are taken.…”
Section: Diagnosis Of Prostate Cancermentioning
confidence: 99%